PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN EDUCAPLAY PADA PEMBELAJARAN IPAS MATERI INDONESIAKU KAYA ALAMNYA - Syiffa Nur Hofifah; Indriyani; Rini Sri Indriani (STKIP Subang, 2025)
Development of Learning Evaluation Using Educaplay in IPAS Learning My Indonesian Rich Material in Nature. This research uses an R&D (Research and Development) approach at Ciawi State Elementary School 03 Bogor Regency. The research subject was a class V student of Ciawi State Elementary School 03 consisting of 25 students. This research was conducted in the even semester of the 2024/2025 academic year. The purpose of this study is to develop a Learning Evaluation Using Educaplay in the Learning of Science Materials Indonesiaku Kaya Alam to determine its feasibility and effectiveness. This research uses the ADDIE (Analysis, Design, Development, Implemantion, Evaluation) method. In this study, a validation test was used for experts, namely media experts, linguists, and material experts. To develop the effectiveness of cognitive ability results, students measured with pre-test and post-test scores.To develop and improve Learning Evaluation using Educaplay, a response from students and teachers is needed. The results of the evaluation by media experts were 98% with the criterion of